1981
DOI: 10.1080/00288233.1981.10420871
|View full text |Cite
|
Sign up to set email alerts
|

Aspect influences on pasture microclimate at Coopers Creek, North Canterbury

Abstract: Rainfall, soil moisture, and soil and air temperatures were measured over five years on north and south aspects (about 25°slope) of a grazed pasture and on the exposed intervening ridge crest at Coopers Creek, North Canterbury (43°IS'S) at about 380 m a.s.l. Solar radiation and wind were measured only on the ridge, and radiation received on north and south slopes was derived from ridge measurements. Potential evapotranspiration on all aspects was calculated from solar radiation and air temperature according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 11 publications
3
24
1
Order By: Relevance
“…Perring (1959) showed that the species composition of chalk grassland at many sites in Britain was strongly influenced by slope and aspect. Two distinct topographic gradients lie behind the observed distribution patterns, namely (i) the tendency of slopes facing the equator (and hence intercepting more direct solar radiation) to be both drier and warmer than those facing away from the equator (Geiger 1965;Påhlsson 1974;Radcliffe & Lefever 1981;Rorison et al . 1986a) and (ii) the tendency for soils on relatively steep (> c .…”
Section: Introductionmentioning
confidence: 99%
“…Perring (1959) showed that the species composition of chalk grassland at many sites in Britain was strongly influenced by slope and aspect. Two distinct topographic gradients lie behind the observed distribution patterns, namely (i) the tendency of slopes facing the equator (and hence intercepting more direct solar radiation) to be both drier and warmer than those facing away from the equator (Geiger 1965;Påhlsson 1974;Radcliffe & Lefever 1981;Rorison et al . 1986a) and (ii) the tendency for soils on relatively steep (> c .…”
Section: Introductionmentioning
confidence: 99%
“…Although these constraints are not severe compared to elsewhere in the world, this hill country is among the driest area of New Zealand, and suffers production loss attributable to water deficit (Radcliffe 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Tussocks may also ameliorate extreme temperatures in their vicinity and reduce soil evaporation, so altering the micro-climate for plants (O'Connor & Lambrechtsen 1964;Radcliffe 1974;Radcliffe & Lefever 1981;Scott 1962;Sewell 1952;Zotov 1938) and influencing the zonation of plant species (Scott 1%1). Shelter from tussocks may also promote growth of introduced cocksfoot (Dactylis glomerata, Radcliffe 1974), and survival of oversown grasses and clovers (Scott & Archie 1976).…”
Section: New Zealand Studiesmentioning
confidence: 99%